Towards phosphorus sustainability in North America: A model for transformational change. Issue 77 (November 2017) - Jacobs, Brent; Cordell, Dana; Chin, Jason; Rowe, Helen
Highlights: Transformation to P sustainability for North America is modelled. Drawing on socio-technical transitions a series of pathways is described. Pathways represent a stakeholder-led vision of improved P sustainability. The contribution of sustainability science to environmental improvement is exemplified. Abstract: Global food production and security rely heavily on finite reserves of newly mined phosphate for fertilizers. However, systemic inefficiencies result in the deposition in aquatic ecosystems of much of the phosphorus mined for food production causing costly eutrophication problems that damage aquatic ecosystems and human health. The Sustainable Phosphorus Alliance (SPA, formerly named North American Partnership for Phosphorus Sustainability) was created to implement sustainable phosphorus solutions through active engagement of stakeholders in both the private and public sectors. This paper describes a conceptual model of transformative change to a sustainable phosphorus system for the North American region. The model emerged from discussions at a series of formal and informal meetings held in conjunction with a 'Future of Phosphorus' event (National Science Foundation's Phosphorus Sustainability Research Coordination Network) and an inaugural SPA Board meeting. Model development drew on the multi-level perspective of socio-technical transitions to develop a series of pathways to a transformed phosphorus system. The uses of the model and transition pathways are discussed in terms of their potential to form an important first step towards the development of a regional vision for improved phosphorus sustainability. The process provides an example of how research in sustainability science can contribute to action on environmental improvement.